Successful reduction of acute puerperal uterine inversion with use of Bakri postpartum balloon - Saha, Divya; Singh, Dipika; Verma, Sarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Acute puerperal inversion is rare but potentially fatal obstetric emergency and prompt recognition will enable immediate repositioning of uterus before it becomes edematous and incarcerated. Manual repositioning along with use of uterine balloon tamponade is simple and effective way for repositioning of inverted uterus as well as prevention of recurrence.